Pengaruh Bermain Perkusi Bambu terhadap Kecerdasan Musikal Anak Di Raudhatul Athfal - Miftahul Khaira; Indra Yeni (Jurnal Family Education, 2021)
This study aims to determine the effect of playing bamboo percussion on the musical intelligence of children in Raudhatul Athfal Arafah Padang. The musical intelligence of children at Raudhatul Athfal Arafah Padang has not developed well, because of the low musical understanding of children in recognizing tempo, it can be seen when children are singing that many do not match the beats played by the teacher with a tambourine musical instrument or when clapping. The limited facilities and infrastructure for playing music for children have resulted in no opportunity for children to develop music playing activities at school. This study uses a quantitative approach with a quaishi experimental design, the data collection technique in this study is an action test on students. This research was conducted at Raudhatul Athfal Arafah Padang which consisted of two classes, one class was used as the experimental class group and the other class was used as the control class group. The experimental class group was 12 people and the control class group was 12 people. The data analysis technique in this study used the Normality Test, Homogeneity Test, and Hypothesis Testing. The results of the Hypothesis Testing in the post-test obtained tcount > ttable where 9.23 > 2.073 as evidenced by the significant level = 0.05 this means that there is a significant difference between the results of the intelligence of children in the experimental class playing bamboo percussion compared to the control class using clap.